Impact of Snow Storms on Habitat and Death of Yunnan Snub-Nosed Monkeys in the Baimaxueshan Nature Reserve, Yunnan, China. (24th October 2012) - Li, Dayong; Ren, Baoping; Hu, Jie; Shen, Yongsheng; He, Xinming; Krzton, Ali; Li, Ming
Abstract : Natural disasters such as snow storms have far-reaching effects on variations in the habitat structure and ecological aspects of non-human primates. Yunnan snub-nosed monkeys ( Rhinopithecus bieti ) inhabit high-altitude forest and endure harsh winters. The effect of heavy snow-storms (January 19 to February 6, 2008) on two large groups of R. bieti (Gehuaqing group and Xiangguqing group) inhabiting Samage Forest in the Baimaxueshan Nature Reserve were assessed. Data on habitat damage were collected between March and May 2008 via field line sampling. The snow storms destroyed 237 big trees in the Samage Forest. The destroyed trees were mostly located along the mountain ridge and valley including Abies georgei, Tsuga dumosa, Pinus yunnanensis and Cyclobalanopsis oxyodon . These trees were important for R. bieti as they provide a dietary source of lichen that is a critical winter fallback food for this primate species, and consequently food availability for R. bieti was reduced. Our results also showed that two juveniles in the Gehuaqing group and three juveniles in the Xiangguqing group were found deceased following the storms. The fact indicates that R. bieti is well adapted to high altitude and strongly seasonal habitat might explain its resilience to heavy snow storms.